2017
DOI: 10.24874/ti.2017.39.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Evaluation of Brake Block Material

Abstract: Keywords:Composite brake block Grey iron brake block Frictional characteristics A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After that, a Ø1 cm ZrO 2 ball was installed on the machine as a counterpart. To begin with, we performed a couple of test measurements, in which we set and changed the test parameters based on data found in the literature [46][47][48][49][50][51]. Based on these preliminary measurements, we selected the final measurement data (Table 3).…”
Section: Tribological Measurementsmentioning
confidence: 99%
“…After that, a Ø1 cm ZrO 2 ball was installed on the machine as a counterpart. To begin with, we performed a couple of test measurements, in which we set and changed the test parameters based on data found in the literature [46][47][48][49][50][51]. Based on these preliminary measurements, we selected the final measurement data (Table 3).…”
Section: Tribological Measurementsmentioning
confidence: 99%
“…The increase of graphite content on the friction material causes more graphite to be distributed on the friction surface. This condition can prevent adhesion and contribute to forming a friction layer on the friction interface [36][37]. The friction layers prevent the hard particles from sticking in the friction interface [35] and inhibit the micro-welding of metallic ingredients [38], thereby protecting the surface from excessive wear [12,39].…”
Section: S/n Ratio and Anova For Wearmentioning
confidence: 99%
“…The filler materials in the composite friction brake have several functions: to reduce production costs, to improve the manufacturing process, and to stabilise the friction coefficient [4,5]. The addition of fillers will lead to an increase in thermal conductivity, which will lower the wear rate during high temperatures in the contact area [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly resistant to fatigue and wear, and has good chemical stability, oil resistance, and vibration absorption [12,13]. This polymer is commonly used as a stabiliser to increase the cross-link and to improve the wear resistance of composite friction brake materials containing asbestos fibres [4]. Ghosh et al [14] reported that NBR could modify phenolic resin and improve friction coefficient performance with the addition of graphite.…”
Section: Introductionmentioning
confidence: 99%